1998
DOI: 10.1021/jm9801713
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Series of Potent and Orally Bioavailable Noncovalent Thrombin Inhibitors That Utilize Nonbasic Groups in the P1 Position

Abstract: As part of an ongoing effort to prepare therapeutically useful orally active thrombin inhibitors, we have synthesized a series of compounds that utilize nonbasic groups in the P1 position. The work is based on our previously reported lead structure, compound 1, which was discovered via a resin-based approach to varying P1. By minimizing the size and lipophilicity of the P3 group and by incorporating hydrogen-bonding groups on the N-terminus or on the 2-position of the P1 aromatic ring, we have prepared a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(88 citation statements)
references
References 7 publications
9
78
0
1
Order By: Relevance
“…[51] The two competing effects nearly cancel each other and the selectivi- [a] Experimental data given as K i values for all the complexes. [27,28] For direct comparison to calculated affinities, conversion to DG was estimated by DG = ÀRTlnK i . www.chemeurj.org ty of binding is thus dominated by the favorable van der Waals energy and nonpolar solvation free energy.…”
Section: H T U N G T R E N N U N G (Complex)-contribution(inhibitor)-mentioning
confidence: 99%
See 2 more Smart Citations
“…[51] The two competing effects nearly cancel each other and the selectivi- [a] Experimental data given as K i values for all the complexes. [27,28] For direct comparison to calculated affinities, conversion to DG was estimated by DG = ÀRTlnK i . www.chemeurj.org ty of binding is thus dominated by the favorable van der Waals energy and nonpolar solvation free energy.…”
Section: H T U N G T R E N N U N G (Complex)-contribution(inhibitor)-mentioning
confidence: 99%
“…As such, many pharmaceutical companies have invested significant efforts to identify less basic and neutral mimics to try to improve the pharmacokinetic properties of these compounds. [25] In this study, molecular dynamics (MD) simulations followed by molecular mechanics generalized Born surface area (MM-GBSA) [26] analyses have been carried out to study the selectivity of two neutral and weakly basic P1 group inhibitors (177 [27] and CDA [28] ) with thrombin and trypsin. Both inhibitors exhibit excellent selectivity of thrombin versus trypsin despite the lack of a strong interaction with the specificity pocket.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bound structure of 29 showed that, compared to the cyclohexylamine of 22, the dichlorophenyl group is rotated in S1 with one of the chlorines sitting over the aromatic group of tyr-228. 71,72 The second chlorine points away from S1 towards bulk solvent without making contact with the enzyme and deletion of this second chlorine results in only a modest drop in potency.…”
Section: • Sandersonmentioning
confidence: 99%
“…In an effort to improve the efficacy without sacrificing oral bioavailability, and using a finding from prior P3 optimization studies, 69 the less lipophilic residue D-cyclohexylglycine was incorporated in the P3 position to give essentially equipotent compound 30. 72 The potency was then enhanced by filling the previously described lipophilic region bounded by the P1 substituent, the aliphatic portion of Glu-192 and the Cys-200/Cys-191 disulfide. This could be accomplished by appending the extra substituent either to the N terminus in the manner of compound 23, or to the 2-position of the P1 group via an ether link.…”
Section: • Sandersonmentioning
confidence: 99%